The Effectiveness of Conflict Management Methods in Improving the Climate of Educational Organizations - Linda Damayanti; Anisa Dwi Rahmandini; Muhammat Junaidi; Izul Magfur Ardana; Hudan Ngisa Anshori (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Conflicts in educational organizations are an inevitable phenomenon. These conflicts can have a positive or negative impact depending on how the conflict is managed. This study aims to analyze the effectiveness of conflict management methods in improving the climate of educational organizations. The research method used is a qualitative approach with a library research approach by examining various relevant scientific literature sources. The results of the study show that effective conflict management methods including collaboration, principle negotiation, mediation, open dialogue, role clarification, and communication training are proven to be able to improve the climate of educational organizations.